2020
DOI: 10.3390/ijms21145016
|View full text |Cite
|
Sign up to set email alerts
|

New Opportunity to Formulate Intranasal Vaccines and Drug Delivery Systems Based on Chitosan

Abstract: In an attempt to develop drug delivery systems that bypass the blood–brain barrier (BBB) and prevent liver and intestinal degradation, it was concluded that nasal medication meets these criteria and can be used for drugs that have these drawbacks. The aim of this review is to present the influence of the properties of chitosan and its derivatives (mucoadhesion, permeability enhancement, surface tension, and zeta potential) on the development of suitable nasal drug delivery systems and on the nasal bioavailabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 135 publications
(295 reference statements)
0
26
0
Order By: Relevance
“…These results are directly correlated with the mucoadhesion study, shown previously ( Section 3.7 ). Where, the amino groups bond ionically with sulfonic acid of the mucus and the amino and hydroxyl groups form hydrogen bonds with the mucus, leading to the reversible opening of the tissue junction, and the permeation of substances through the nasal epithelium is increased [ 52 ]. The impact of chitosan on permeation was evaluated to its potentiating effect on the permeation of the peptide through the layers of the nasal mucosa, as also observed in other studies [ 14 , 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…These results are directly correlated with the mucoadhesion study, shown previously ( Section 3.7 ). Where, the amino groups bond ionically with sulfonic acid of the mucus and the amino and hydroxyl groups form hydrogen bonds with the mucus, leading to the reversible opening of the tissue junction, and the permeation of substances through the nasal epithelium is increased [ 52 ]. The impact of chitosan on permeation was evaluated to its potentiating effect on the permeation of the peptide through the layers of the nasal mucosa, as also observed in other studies [ 14 , 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…Due to its low toxicity, biodegradability and biocompatibility, chitosan has been increasingly studied in a wide range of pharmaceutical, biomedical, and biotechnological fields, including gene therapy, bone regeneration, food industry, and agriculture [ 45 , 46 ]. Chitosan displays hemostatic and hastening wound healing effects, anti-hypercholesterolemic effects, bioactivity, chemotactic actions, antimicrobial activity, immunostimulation, enzymatic biodegradability, mucoadhesion, andepithelial permeability [ 47 , 48 , 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…chitosan as an anti-influenza agent (Zheng et al 2016;Mohammadi et al 2020;Popescu et al 2020). Hassan et al (2016) tested the antiviral activity of chitosan against Rift Valley Fever virus (RVFV), Herpes Simplex-1 (HSV-1) and Coxsackie viruses.…”
Section: Accepted Articlementioning
confidence: 99%